Impact of Type and Duration of Alcohol Consumption on the Severity and Outcomes of Alcoholic Liver Disease in Women - Dr. Suraj Bhutada; Dr. Snehal Pallod (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The prevalence of alcoholic liver disease (ALD) in women has increased over the past decades, mirroring shifts in drinking patterns and social norms. Women are known to be more susceptible to alcohol-related liver injury at lower consumption thresholds than men. Yet, the specific impact of the type and duration of alcohol intake on ALD severity, progression, and clinical outcomes in women remains understudied. Methods: In this prospective observational study, we enrolled 160 adult women with ALD from a tertiary care center. Detailed alcohol use histories, including type of alcoholic beverage (wine, Desi Darus, beer) and duration of heavy drinking, were obtained. Baseline assessments included clinical evaluation, liver function tests, and imaging studies. Patients were followed for two years to assess disease progression and outcomes, including decompensation events, hospitalization, and mortality. Multivariate analyses examined the relationships between beverage type, duration of heavy drinking, severity of ALD (fibrosis stage, MELD score), and clinical endpoints. Results: At baseline, mean age was 48.5 ± 9.2 years. Women who primarily consumed Desi Darus had more advanced fibrosis and higher MELD scores compared to those favoring wine or beer (p<0.01). A prolonged duration (>10 years) of heavy alcohol intake correlated with higher rates of cirrhosis and hepatic decompensation (p<0.001). After adjusting for confounders such as BMI and viral co-infections, both beverage type and drinking duration independently predicted disease severity. During follow-up, patients with long-term Desi Darus intake experienced higher rates of variceal bleeding and hepatic encephalopathy, leading to increased hospitalizations and mortality. Conclusion: In women with ALD, both the type and duration of alcohol consumption significantly influence disease severity and clinical outcomes. Desi Darus consumption and prolonged heavy drinking pose a greater risk for advanced liver damage and worse prognosis. Recognizing these patterns may guide more tailored interventions and preventive strategies.